Cross-Cultural Adaptation and Psychometric Testing of the Urdu version of Copenhagen Neck Functional Disability Scale: Psychometric Testing of CNFDS - Naz, Somiya; Farooq, Muhammad Nazim; Iqbal, Ahsnat; Naqvi, Tahniat Zehra; Rasul, Sahibzada M. Fazal ur (Pakistan Journal of Health Sciences, 2023)
Neck pain is one of the common problems among people. Different measures have been developed to assess the rate of neck pain and disabilities. Patients with neck pain frequently use and easily understand the Copenhagen neck functional disability scale (CNFDS). Objective: To cross-culturally adapt and translate CNFDS into Urdu and examine the psychometric properties of Urdu version of CNFDS (CNFDS -U) in individuals with non-specific neck pain (NSNP). Methods: The CNFDS was translated into Urdu and cross-culturally adapted in compliance with the established standards. This study was carried out on 200 patients having neck pain and 50 healthy respondents. The CNFDS-U, Neck Bournemouth Questionnaire (NBQ), and Neck Pain Disability Index Urdu version (NDI-U) were all completed by a combined 200 individuals with NSNP and 50 healthy subjects. The patients with NSNP completed the aforementioned questionnaires and Global Rating of Change Scale (GROC) following three weeks of physiotherapy. CNFDS-U was evaluated for psychometric testing. Results: The CNFDS-U shows excellent internal consistency (α = 0.84) and test-retest reliability (ICC2,1 =0.97). Regarding construct validity, moderate correlations exist between CNFDS-U and NBQ (r=0.51, p<0.001) and CNFDS-U and NDI-U (r=0.64, p<0.001). Its responsiveness was demonstrated by a statistically significant difference in CNFDS-U change scores between improved and stable groups (p< 0.001). Conclusions: The CNFDS-U is a valid, reliable, and responsive scale for evaluating NSNP in populations that can understand Urdu.